Internationalization of Legal Education in Indonesia: Insights from Faculty of Law Universitas Negeri Semarang - Sudijono Sastroatmodjo; Suhadi, Suhadi (The Indonesian Journal of International Clinical Legal Education, 2019)
In today’s global era, the internationalization of higher education has been defined as “the process of integrating an international, intercultural, and global dimension into the goals, teaching and learning, research, and service functions of a university or higher education system” (Knight, 2014). Within this framework, the internationalization of legal education refers to the application of these processes in law schools around the world. Several factors contribute to the growing need for internationalized legal education, including the increasing demand for transnational legal practice and the emergence of legal issues that extend across international boundaries. This article examines the internationalization of legal education in Indonesia by focusing on the international program offered by the Faculty of Law, Universitas Negeri Semarang. It analyzes the strengths and opportunities of the program, as well as its weaknesses and threats. Although the international program at Universitas Negeri Semarang may not fully represent similar programs at other Indonesian law faculties, it provides valuable insight into how a public university implements internationalization within legal education. The article begins with a discussion of theoretical perspectives on the internationalization of legal education. It then outlines the rationale for internationalizing legal programs and considers how such efforts should be implemented within the Indonesian context. Following this, the article presents a critical analysis of the international law program at Universitas Negeri Semarang, identifying key strengths and weaknesses. Finally, it offers recommendations aimed at improving the quality and effectiveness of international programs in Indonesian law faculties.